2019
DOI: 10.1177/0963689719833303
|View full text |Cite
|
Sign up to set email alerts
|

The Autonomic Innervation and Uterine Telocyte Interplay in Leiomyoma Formation

Abstract: The autonomic innervation of the uterus is involved in multiple pathophysiological processes in both humans and animals. Pathological conditions such as adenomyosis or inflammatory pelvic disease are usually accompanied by significant alterations in uterine innervation. In the current study, we focused on autonomic innervation of uterine fibroids, the identification of recently described interstitial cells, telocytes, and the possible interplay between these structures. In this work, uterine telocytes were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 57 publications
3
17
0
1
Order By: Relevance
“…A recent study shows, for the first time, that there is an interplay between telocytes and autonomic innervation in leiomyomata [92]. TCs decreased in numbers in the leiomyomatous myometrium, suggesting a role for these cells in the control of the microenvironment [92].…”
Section: Telocytes In Uterine and Tubal Diseasesmentioning
confidence: 98%
“…A recent study shows, for the first time, that there is an interplay between telocytes and autonomic innervation in leiomyomata [92]. TCs decreased in numbers in the leiomyomatous myometrium, suggesting a role for these cells in the control of the microenvironment [92].…”
Section: Telocytes In Uterine and Tubal Diseasesmentioning
confidence: 98%
“…TCs also form neurological connections. Previous studies have shown the relationship between TCs and uterine autonomic nerves 17 .…”
Section: Introductionmentioning
confidence: 95%
“…The aforementioned epigenetic associations of CACNA1A support the gene's involvement in epigenetics of tumorogenesis. Interestingly, a previous study demonstrated that innervation of the uterus is involved in multiple pathophysiological processes and suggests that autonomic innervations together with interstitial telocytes are involved in the microenvironmental imbalance of UL [48]. Moreover, the difference in adrenergic and cholinergic innervation between normal myometrium and fibroid tumors demonstrates the pivotal role of the neuronal component in the formation of UL [48].…”
Section: Discussionmentioning
confidence: 99%